Designing Sustainable City: Feasibility of Gamification-Integrated STEM-Based Science Learning Tools - Anugrah Putri Nur'aini; Shelly Efwinda; Muhammad Amiq Zahidsyahtya; Erna Sari; Atin Nuryadin; Nurul Fitriyah Sulaeman (Department of Physics Education, Universitas Mataram, 2026)
– This study aims to develop and validate STEM-based learning tools integrated with Game-Based Learning themed